A band-modulation device in advanced FDSOI technology: Sharp switching characteristics. (November 2016) - El Dirani, Hassan; Solaro, Yohann; Fonteneau, Pascal; Legrand, Charles-Alex; Marin-Cudraz, David; Golanski, Dominique; Ferrari, Philippe; Cristoloveanu, Sorin
Abstract: A band-modulation device is demonstrated experimentally in advanced FDSOI (Fully Depleted SOI). The Z 2 -FET (Zero Impact Ionization and Zero Subthreshold Slope FET) is a very recent sharp switching device which achieves remarkable performance in terms of leakage current and triggering control. The device is fabricated with Ultra-Thin Body and Buried Oxide (UTBB) Silicon-On-Insulator (SOI) technology, features an extremely sharp on-switch, low leakage and an adjustable triggering voltage ( V ON ). The Z 2 -FET operation relies on the modulation of electrons and holes injection barriers. In this paper, we show, for the first time, experimental data obtained with the most advanced FDSOI node.